Sintaksis dalam Pembelajaran Bahasa Indonesia : Tantangan dan Solusi di Sekolah - Mirna Putri Aulia; Sari Rahmadani; Sri Rahma Haryanti; Selvisari Br Ginting; Frina Barus (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This article explores the challenges and solutions in teaching syntax in Indonesian language education at schools. Syntax, as a crucial part of language structure, is often perceived as difficult and boring by students due to its theoretical and non-contextual delivery. Based on a literature review of scholarly journals and national books, it was found that students’ understanding of sentence structure remains low, affecting their writing and speaking skills. Teachers also face obstacles in developing effective and engaging teaching strategies. To address these issues, this article proposes several solutions, such as the use of communicative approaches, interactive learning media, and continuous professional development for teachers. It is hoped that with more contextual and practical methods, syntax learning can become more meaningful and enjoyable for students.